2014
DOI: 10.1103/physrevlett.113.107203
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Induced Skyrmion Distortion and Giant Lattice Rotation in the Magnetoelectric InsulatorCu2OSeO3

Abstract: Uniquely in Cu 2 OSeO 3 , the Skyrmions, which are topologically protected magnetic spin vortexlike objects, display a magnetoelectric coupling and can be manipulated by externally applied electric (E) fields. Here, we explore the E-field coupling to the magnetoelectric Skyrmion lattice phase, and study the response using neutron scattering. Giant E-field induced rotations of the Skyrmion lattice are achieved that span a range of ∼25°. Supporting calculations show that an E-field-induced Skyrmion distortion li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
182
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(192 citation statements)
references
References 39 publications
(71 reference statements)
6
182
2
Order By: Relevance
“…The emergence of the skyrmion lattice phase was identified in the close vicinity of the paramagnetic-helical phase boundary of cubic chiral helimagnets, known as B20 compounds with a P 2 1 3 space group [3][4][5][6][7]. Cu 2 OSeO 3 , belonging to the same space group with a different crystal structure [8] is an insulating material demonstrated to host skyrmions [9,10], with a magnetoelectric character [11][12][13][14]. Since their experimental discovery, skyrmions have attracted much attention owing to their potential application as magnetic bits in high-capacity and low-consumption memory devices [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the skyrmion lattice phase was identified in the close vicinity of the paramagnetic-helical phase boundary of cubic chiral helimagnets, known as B20 compounds with a P 2 1 3 space group [3][4][5][6][7]. Cu 2 OSeO 3 , belonging to the same space group with a different crystal structure [8] is an insulating material demonstrated to host skyrmions [9,10], with a magnetoelectric character [11][12][13][14]. Since their experimental discovery, skyrmions have attracted much attention owing to their potential application as magnetic bits in high-capacity and low-consumption memory devices [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmion motion can be directly observed with Lorentz microscopy 7,10 or deduced from changes in the transport properties, permitting the construction of effective skyrmion velocity versus applied force curves that show that the skyrmion velocity increases with increasing current 20 . Other methods to move skyrmions include the use of temperature gradients [27][28][29][30][31] , electric fields 32,33 , and coupling to a magnetic tip 15 .…”
Section: Introductionmentioning
confidence: 99%
“…30 ) and, more importantly, an electric field is easier to manipulate than a temperature gradient. It has also been shown that in multiferroic materials, which include Cu 2 OSeO 3 , skyrmion textures have an intrinsic dipole moment which enables them to couple to to the gradient of electric field 29,35,36,45 . Regardless of the difficulty of applying a gradient in electric field, the estimated Hall velocity v H in our approach is two orders of magnitude greater than v H due to magnetoelectric coupling 29 , where v H ≈ (λR S /2πS )∆E ∼ 10 −3 mm/s with R S = 25 nm, dipolar coupling λ ∼ 10 −33 ≈ C · m 34 , and field strength difference ∆E ∼ 10 2 V/m.…”
mentioning
confidence: 99%